Proof: Get New State 4

Let's prove the following theorem:

if expression state at time 4 = "return", then expression state at time 5 = "iterate_args"

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 expression state at time 4 = "return"
Proof Table
# Claim Reason
1 expression state at time (4 + 1) = "iterate_args" if expression state at time 4 = "return", then expression state at time (4 + 1) = "iterate_args"
2 4 + 1 = 5 4 + 1 = 5
3 expression state at time (4 + 1) = expression state at time 5 if 4 + 1 = 5, then expression state at time (4 + 1) = expression state at time 5
4 expression state at time 5 = "iterate_args" if expression state at time (4 + 1) = expression state at time 5 and expression state at time (4 + 1) = "iterate_args", then expression state at time 5 = "iterate_args"

Comments

Please log in to add comments